Tracking the Evil Eye: Trait Anger and Selective Attention within Ambiguously Hostile Scenes - Wilkowski, Benjamin M. (2007)
Previous research has shown that trait anger is associated with biases in attention and interpretation, but the temporal relation between these two types of biases remains unresolved. Indeed, two very different models can be derived from the literature. One model proposes that interpretation biases emerge from earlier biases in attention, whereas the other model proposes that hostile interpretations occur quickly, even prior to the allocation of attention to specific cues. Within the context of integrated visual scenes of ambiguously intended harm, the two models make opposite predictions that can be examined using an eye-tracking methodology. The present study (N = 45) therefore tracked participants’ allocation of attention to hostile and non-hostile cues in ambiguous visual scenes, and found support for the idea that high anger individuals make early hostile interpretations prior to encoding hostile and non-hostiles cues. The data are important in understanding associations between trait anger and cognitive biases.